Simulation and performance improvement of a reverse logistics system for waste electrical and electronic equipment: a case study in Italy. (18th July 2019) - Bottani, Eleonora; Montanari, Roberto; Rinaldi, Marta
This paper presents a simulation study to evaluate the performance of a real waste electrical and electronic equipment (WEEE) management system of the north of Italy and to investigate alternative scenarios to enhance its effectiveness. A detailed simulation model was developed in Microsoft Excel TM to reproduce the behaviour of the different players of the system. To this end, two real players, i.e., a WEEE collection company and a treatment plant both located in the north of Italy, were preliminarily observed. Data about the incoming flow of WEEE and the production of recycled goods was retrieved from direct observations. Specific key performance indicators were determined and used to evaluate the performance of the existing network and of some alternative configurations. As it grounds on a real WEEE reverse logistics system, this study provides interesting proposals for future actions on WEEE management.